Il vescovo di Roma, primate d’Italia - Parlato, Vittorio (Cultura giuridica e diritto vivente, 2020)
[The Bishop of Rome, primate of Italy] Historical and political significance, the legal role of the primate office in the Catholic hierarchy. The special relationship of the Italian ecclesiastical reality with the Roman Pontiff and the connection of the Italian episcopate to the Roman See. The legal connotation of the Hungarian and Italian primacy, the current primary action.